Posterior Mediastinum Ganglioneuroma: a Case Report - Mileny Acosta Fonseca; Elsy Roxana Geroy Moya; Tamara Estrada Sánchez (Revista Finlay, 2022)
Neuroectodermal tumors are the main cause of mediastinal tumors. Of these, the ganglioneuroma is the most benign and the least frequent, with an incidence of 1 in 100,000 children. It occurs predominantly in childhood with a mean presentation at age seven. Most of these tumors are asymptomatic and diagnosed incidentally. The 43 % of them showing intrathoracic manifestation and located in the sympathetic ganglia of the posterior mediastinum. Imaging studies provide advantages for the location, size and extent of the tumor. These tests are of great benefit to the surgeon. The prognosis is generally favorable, which is a sign of good prognosis when it appears after five years of age and when it is located in the posterior mediastinum. The case of a patient who underwent thoracoscopy with total resection of the tumor, with a favorable evolution during her follow-up is presented. This patient was diagnosed with a ganglioneuroma in the posterior mediastinum. A literature review was carried out regarding this case. This report is presented because ganglioneuroma is a rare benign tumor in children.